Attitudes toward Female Circumcision among Men and Women in Two Districts in Somalia: Is It Time to Rethink Our Eradication Strategy in Somalia? - Abdi A. Gele; Bente P. Bø; Johanne Sundby (Obstetrics and Gynecology International)
Somalia has the highest global prevalence (98%) of female circumcision (FC), and, despite a long history of abandonment efforts, it is not clear as to whether or not these programmes have changed people’s positive attitudes toward the practice. Against this background, this paper explores the attitudes of Somalis living in Hargeisa and Galkayo districts to the practice of FC. Methods. A purposive sampling of 24 Somalis, including activists and practitioners, men and women, was conducted in Somalia. Unstructured interviews were employed to explore the participants' knowledge of FC, their attitudes toward the continuation/discontinuation of the practice, and the type they want to continue or not to continue. Result. The findings of this qualitative study indicate that there is a strong resistance towards the abandonment of the practice in Somalia. The support for the continuation of Sunna circumcision is widespread, while there is a quite large rejection of Pharaonic circumcision. Conclusion. Therefore, since the “zero tolerance policy” has failed to change people’s support for the continuation of the practice in Somalia, programmes that promote the pinch of the clitoral skin and verbal alteration of status, with the goal of leading to total abandonment of FC, should be considered for the Somali context.